Calibration and data analysis strategies for enhanced 21-cm EoR limits with the MWA - Chege, James Kariuki (Curtin University, 2022)
This thesis targets observations of the 21 cm signal emitted by neural hydrogen during the early stages of the Universe using data from the Murchison Widefield Array radio telescope. The detection of this elusive signal is challenging, and this thesis tackles the obstacles involved, investigating current methods and proposing novel ones. The work presented by this research is therefore another step towards a complete understanding of the history of our Universe.